2023
DOI: 10.1523/eneuro.0385-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Risky Decision Making and Associated Neural Circuitry in a Rat Model

Abstract: Altered decision making at advanced ages can have a significant impact on an individual’s quality of life and the ability to maintain personal independence. Relative to young adults, older adults make less impulsive and less risky choices; although these changes in decision making could be considered beneficial, they can also lead to choices with potentially negative consequences (e.g., avoidance of medical procedures). Rodent models of decision making have been invaluable for dissecting cognitive and neurobio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 91 publications
(139 reference statements)
0
7
0
Order By: Relevance
“…Fewer trials could reflect reduced motivation to respond for food rewards or greater sensitivity to reward devaluation as rats become sated during each test session. Normal aging is associated with lower motivation to work for food rewards in progressive ratio tasks ( Hernandez et al, 2017 ; Jackson et al, 2021 ; Orsini et al, 2023 ) whereas pre-feeding to induce satiety and devalue food rewards is similar between young adult and aged rats ( Samson et al, 2014 ). To the best of our knowledge, no studies have investigated the effect of CVS on either progressive ratio or outcome devaluation tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer trials could reflect reduced motivation to respond for food rewards or greater sensitivity to reward devaluation as rats become sated during each test session. Normal aging is associated with lower motivation to work for food rewards in progressive ratio tasks ( Hernandez et al, 2017 ; Jackson et al, 2021 ; Orsini et al, 2023 ) whereas pre-feeding to induce satiety and devalue food rewards is similar between young adult and aged rats ( Samson et al, 2014 ). To the best of our knowledge, no studies have investigated the effect of CVS on either progressive ratio or outcome devaluation tasks.…”
Section: Discussionmentioning
confidence: 99%
“…RECORD Manual tmazes 5,10,15,25 Automatic tmazes 12,13 Virtual reality tasks 14,59 Operant Chambers (lever pressing and nose pokes) 3,22,23,28,49,60 Wheel Displacement…”
Section: Table 1: Methods Comparison Featuresmentioning
confidence: 99%
“…Some operant conditioning tasks use touchscreens as an alternative to traditional nose-poke compartments 21 ; others may extend the experimental space so the rodent traverses the chamber when deciding 22 , while some tasks utilize auditory cues to signal the presence of a reward or cost 19 .All the aforementioned methods are excellent tools for studying different facets of DM. Nonetheless, most of these methods are used to analyze one or two levels of rewards and costs at a time 3,5,23 . A task environment that enables the implementation of multiple reward and cost trade-offs within one behavioral session heightens a system's ability to detect individual differences, as well as enabling the comprehensive identification of DM phenotypes that are overrepresented in animal models of psychiatric disorders 11,24 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The greater risk aversion is observed in older humans and highlights age-related alterations in brain connectivity. FMRI analyses demonstrated that, on the whole, aged rats exhibited higher functional connectivity compared to young rats, especially among brain regions associated with risky decisionmaking, such as the basolateral amygdala, orbitofrontal cortex, and ventral tegmental area [22].…”
Section: Neuroimaging Findingsmentioning
confidence: 97%